"At First I Wouldn't Talk so Much…": Coaching and Associated Changes in Language-Supportive Self-Efficacy among Infant/Toddler Educators. Issue 8 (17th November 2021) - Gardner-Neblett, Nicole; De Marco, Allison; Sexton, Sarah
ABSTRACT: Developing strong language and communication skills in the first years of life provides young children with a foundation for a number of positive outcomes, including school readiness, early literacy skills, and self-regulation. High quality language supports in early childhood education programs are key to this development. Part of providing these high-quality language supports involves educators perceiving themselves as efficacious in their capability to support young children's language development. Using mixed methods, this study examines the extent to which there are changes in educators' language-focused self-efficacy after participating in professional development program focused on promoting infant/toddler language development. We examine the changes across two groups: (1) educators who participated in a workshop focused on infant/toddler language development and (2) educators who participated in the same workshop plus one-on-one practice-based coaching. Results suggest that participation in the workshop plus coaching compared to the workshop alone was related to greater growth in self-efficacy in language modeling and instructional practices. In follow-up interviews, coached educators reported on their perceptions of impact of the program on their practices and interactions with children. Implications for future research and practice are discussed.